Diagnosis of Chronic Obstructive Pulmonary Disease (COPD) in Shohada Tajrish Hospital - Hashemi, Hoda; Aliakbari, Fereshteh; shariatpanahi, Samira; Hashemi, Reza (Archives of Men’s Health, 2020)
Introduction: This paper aims to determine the effectiveness and sensitivity of peak expiratory flow in early diagnosis of chronic obstructive pulmonary disease (COPD). In view of high cost and unavailability of spirometry and the ever-increasing prevalence of COPD as a result of cigarette smoking, this study can do much to lighten the economic burden in national health system. Materials and Methods: We examined 250 patients taking spirometry test in Shohadaye Tajrish Hospital during 2008, chosen by simple random sampling method. COPD was defined as FEV/FVC<70% according to existing resources. PEF values smaller than 80% were considered as abnormal based on ATS criteria. We assessed PEF sensitivity in comparison with FEV1/FVC. Results: COPD prevalence among spirometry tests was 21.2%. Out of the patients, 76.27% were male and 92.9% were older than 40. PEF sensitivity was 74% and its specificity was 97.5%. Discussion: The higher COPD prevalence among men may be explained by higher cigarette smoking rate among men than in women in our country. Moreover, COPD occurrence risk increases with age. Conclusion: The positive predictive value of PEF compared with EFV1/FVC reveals that this test is an appropriate diagnostic tool which can diagnose COPD earlier than EFV1/FVC.